Reinforcement effect of graphene oxide in glass fibre/epoxy composites at in-situ elevated temperature environments: An emphasis on graphene oxide content. (April 2017) - Prusty, Rajesh Kumar; Ghosh, Sohan Kumar; Rathore, Dinesh Kumar; Ray, Bankim Chandra
Abstract: The unique and exceptional properties of graphene based nanofillers have impelled material scientists for their possible exploitation in fibrous polymeric composites. Present investigation elucidates the effect of environmental temperature on the mechanical response of glass fibre/epoxy (GE) composite loaded with a range of graphene oxide (GO) content. Incorporation of 0.5 wt.% GO in GE exhibited 21.1% improvement in flexural strength. The state of interface (both GO/epoxy and glass fibre/epoxy) and its impact on the flexural behaviour at various testing temperatures has been discussed. The viscoelastic properties of all the materials have been further evaluated in the temperature range of 40–200 °C. The Weibull design parameters have been analysed as a function of GO content and testing temperature. Scanning electron microscope (SEM) analysis of fractured surfaces has been carried out to comprehend various interfacial strengthening and failure micro-mechanisms.